The effect of IL-7 on memory CD8+ T cell survival and function during health and HIV disease - O'Connor, Alison (University of Ottawa (Canada), 2010)
Memory CD8+ T cells proliferate and gain effector function in response to antigen stimulus. It is possible that IL-7 may enhance antigen-mediated CD8+ T cell recall response, since IL-7 is required during a primary immune response. During HIV infection, CD8+ T cell function is impaired, and this could be due to reduced IL-7 activity on CD8 + T cells. In the present study, the effect of IL-7 on antigen-mediated proliferation and function was evaluated in HIV- and HIV+ individuals. IL-7 enhanced antigen-mediated proliferation of the CD8 +CD45RA-CD127+ T cells, but it did not significantly alter IFN-gamma production or CD107a/b expression. In HIV + individuals, CD8+CD45RACD127+ T cells did not significantly proliferate in response to IL-7. These data indicate that IL-7 can enhance certain aspects of memory CD8+ T cell function, and IL-7 activity is impaired in HIV infection. These findings are relevant to the ongoing studies of HIV pathogenesis and of IL-7 as a therapeutic in HIV infection and other diseases.
Keywords: Biology, Microbiology.; Health Sciences, Immunology.